Calmodulin and signal transduction - Van Eldik, Linda J.; Watterson, D. Martin (Academic Press, 1998)
This book focuses on emerging themes in the molecular mechanisms of calcium signal transduction through calmodulin-regulated pathways. It provides the reader with selected examples and experimental precedents that underlie current models of cell regulation through calmodulin-regulated pathways and their linkage with other regulatory pathways. Highlights: * Molecular mechanisms of calcium signal transduction through calmodulin-regulated enzymes * Selected case studies and precedents related to molecular mechanisms * Protein-protein recognition between calmodulin and the enzymes it regulates * Cross-talk and interdigitation with other signal transduction pathways.